Intra-Herb Interactions: Primary Metabolites in Coptidis Rhizoma Extract Improved the Pharmacokinetics of Oral Berberine Hydrochloride in Mice - Zhao, Jing; Zhou, Ting; Lu, Jing-Ze; Ye, Dan; Mu, Sheng; Tian, Xin-Hui; Zhang, Wei-Dong; Ma, Bing-Liang (Frontiers in Pharmacology, 2021)
Primary plant metabolites can be used for artificial preparation of natural deep eutectic solvents (NADESs), which have strong dissolving capacity, good biocompatibility, and biodegradability. In this study, for the first time, we verified that NADESs were present in Coptidis Rhizoma extract and systematically investigated its effects and mechanisms on the pharmacokinetics of oral berberine hydrochloride (BBR), a co-existing bioactive constituent. First, three LC-MS/MS based methods were established and fully validated to determine the levels of 11 primary metabolites in Coptidis Rhizoma extract. According to the weight ratio of four major primary metabolites in the Coptidis Rhizoma extract, a stable “endogenous” NADES was prepared using the heating method by the addition of 350 μL of water to 1307.8 mg of the mixture of malic acid (490.5 mg), glucose (280.6 mg), sucrose (517.7 mg), and choline chloride (19.0 mg). The prepared NADES showed significant acute toxicity in mice and cytotoxicity in MDCK-MDR1 cells. However, after being diluted 10 times or 100 times, the NADES had no significant acute toxicity or cytotoxicity, respectively. The dilutions of the NADES significantly increased the water solubility of BBR, reduced its efflux in gut sacs and MDCK-MDR1 cell monolayer, and improved its metabolic stability in intestinal S9. In addition, the NADES dilutions reversibly opened the tight junctions between the enterocytes in the gut sacs. Moreover, the NADES dilutions significantly improved the exposure levels of BBR in the portal vein and livers of mice that were administered oral BBR. Malic acid was identified as a major component in the NADES in terms of solubility, acute toxicity, cytotoxicity, and pharmacokinetic-improving effects on oral BBR. In conclusion, the primary metabolites of Coptidis Rhizoma extract could form “endogenous” NADES, and its dilutions improve the pharmacokinetics of oral BBR. This study demonstrates the synergistic interaction of the constituents of Coptidis Rhizoma extract and the potential use of the NADES dilutions in oral BBR delivery.